Constructing graphite-like carbon nitride modified hierarchical yolk–shell TiO2 spheres for water pollution treatment and hydrogen production. Issue 5 (14th January 2016) - Jiang, Zhifeng; Zhu, Chengzhang; Wan, Weiming; Qian, Kun; Xie, Jimin
Abstract : Here we present a new visible light active composite based on porous graphitic carbon nitride decorated hierarchical yolk–shell TiO2 spheres for water pollution treatment and H2 evolution. Abstract : Graphitic carbon nitride (g-C3 N4 ) was hybridized by hierarchical yolk–shell TiO2 spheres via a solvothermal method by mixing the as-prepared g-C3 N4 with the precursor of the TiO2 yolk–shell spheres in dimethylformamide (DMF). The introduction of DMF made the TiO2 yolk–shell spheres to be dispersed well on the surface of g-C3 N4, thus improving the specific surface area of the materials. The g-C3 N4 has a unique two-dimensional layered structure, which is favorable for hybridizing with TiO2 . The sufficient contact interface between TiO2 and g-C3 N4 could be beneficial to the separation of photogenerated charges. Multiple reflections of light within the interior cavities of titania microspheres with a yolk–shell structure can increase their light absorption. The photocatalytic experimental results indicated that the as-prepared composite TiO2 /g-C3 N4 (TCN) showed enhanced photocatalytic activities compared with pure TiO2 and g-C3 N4 . A suitable combination of g-C3 N4 with TiO2 produced the highest photocatalytic activity. Moreover, the photocatalytic activity of TCN with a yolk–shell structure is higher than that of TiO2 /g-C3 N4 without a yolk–shell structure. Based on our experimental results, a possible photocatalytic mechanism with holes and superoxide radical species as the main active species in photocatalysis was proposed. The TCN photocatalysts prepared in this case, with high photocatalytic activity and high stability, were a promising candidate for possible practical application in industrial production.